Study of Memory Effect in an EOQ Model with Fractional Polynomial Demand Rate Under Fuzzy Environment - Pakhira, Rituparna; Ghosh, Uttam; Sarkar, Susmita; Mishra, Lakshmi Narayan (Discontinuity, Nonlinearity, and Complexity, 2026)
In current years, fractional calculus has received much attention because it can include memory effect to the inventory model. In the paper, fractional order derivative and integration have been applied to include the memory dependency to the polynomial type demand rate inventory model under the fuzzy environment. The advantage of fractional order derivative and integration have been applied to the EOQ model taking fuzzy environment. Inventory cost parameters, for example holding cost, purchasing cost and ordering cost are thought to be triangular fuzzy numbers. Two type memory indices (i) differential memory index, (ii) integral memory index have been established where differential memory index is associated with the fractional order derivative and integral memory index is associated with the fractional order integration. Defuzzification has been considered using graded mean integration method and signed distance method. Numerical examples and graphical presentations are considered to explain importance of the work.